Squaric acid as a new chemoselective moiety for mass spectrometry-based metabolomics analysis of amines. Issue 5 (17th August 2021) - Lin, Weifeng; Yang, Zhen; Kaur, Amanpreet; Block, Annika; Vujasinovic, Miroslav; Löhr, J.-Matthias; Globisch, Daniel
Abstract : First application of squaric acids with excellent stability and chemoselective reactivity in mass spectrometry-based metabolomics analysis of amine-containing metabolites. Abstract : The investigation of microbiome-derived metabolites is important to understand metabolic interactions with their human host. New methodologies for mass spectrometric discovery of undetected metabolites with unknown bioactivity are required. Herein, we introduce squaric acid as a new chemoselective moiety for amine metabolite analysis in human fecal samples.